Preclinical pharmacokinetics and biodistribution of Anticancer Dinuclear Palladium(II)-Spermine Complex (Pd2Spm) in mice - Vojtek, Martin (2022)
Palladium-based compounds are regarded as potential analogs to platinum anticancer drugs with improved properties. The present study assessed the pharmacokinetics and biodistri bution of a dinuclear palladium(II)-spermine chelate (Pd2Spm), which has previously been shown to possess promising in vitro activity against several therapy-resistant cancers. Using inductively coupled plasma-mass spectrometry, the kinetic profiles of palladium/platinum in serum, serum ultrafiltrate and tissues (kidney, liver, brain, heart, lungs, ovaries, adipose tissue and mammary glands) were studied in healthy female Balb/c mice after a single intraperitoneal bolus injection of Pd2Spm (3 mg/kg bw) or cisplatin (3.5 mg/kg bw) between 0.5 and 48 h post-injection. Palladium in serum exhibited biphasic kinetics with a terminal half-life of 20.7 h, while the free palladium in serum ultrafiltrate showed a higher terminal half-life than platinum (35.5 versus 31.5 h). Palladium was distributed throughout most of the tissues except for the brain, with the highest values in the kidney, followed by the liver, lungs, ovaries, adipose tissue and mammary glands. The in vitro cellular accu mulation was also evaluated in breast cancer cells, evidencing a passive diffusion as a mechanism of Pd2Spm’s cellular entry. This study reports, for the first time, the favorable pharmacokinetics and biodistribution of Pd2Spm, which may become a promising pharmacological agent for cancer treatment.